A multiplicidade de áreas de atuação do orientador educacional e implicações para a sua formação - Cavalcante, Lucíola Inês Pessoa (1979)
This study was done by means of bibliographic consultation focusing on the multiple arees in which the counselor acts and implications that it brings to his formation and professional activity. The continuous expansion of the counselor's area of work and the demands on his professional formation and activity, in a historical view, were detected by an analysis of legal documents and regulations of the Ministery of Education and Culture. Vocational guidance, counselin& the integration of guidance. and curriculum, guidance in industry and group counseling,.all of which are areas demanding more attention from educational counselors, were studied. In this study, the complexity a~d high value of the counselor's job was given a sp~cial focus, as his role requires, . not only personal qualities and an adequate technical and scientific background, but also ~ permanent search for functional ways which will enable him to attend the large number of requests often made to him. From a theoretical point of view, the formation of a cbunselor is poor; moreover, it is often insufficien~ which points to the need for urgent changes. It was finally proposed tha the educational ~ounselors should limit their field of work, that is, in their professional activities they should dedicate themselves to just one particular area of work.